The Effect of Hospital Image, Perceived Medical Quality, Word of Mouth on The Intention to Visit Again at The Internal Medicine Polyclinic of Ciawi Hospital - Hansel Wijaya, Nathanael Ryan; Cokki, Cokki (Green Publisher Indonesia, 2025)
This study aims to examine how hospital image, perceived medical quality, and word of mouth affects patient revisit intention at the Internal Medicine unit at Ciawi Regional Hospital, Bogor Regency. The research employs a descriptive design with a cross-sectional approach, utilizing 19 indicators and a sample of 227 respondents. Data analysis is conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method, which includes outer model analysis, inner model analysis, and hypothesis testing. The findings indicate a significant relationship between hospital image and patient revisit intention also word of mouth and patient revisit intention. Additionally, perceived medical quality positively impacts hospital image and word of mouth, while word of mouth also significantly influences hospital image.